KEPATUHAN KONSUMSI SUPLEMEN GIZI BERBASIS LIPID DOSIS KECIL PADA BAYI DI PERDESAAN, KABUPATEN BANGKALAN - Muslihah, Nurul; Khomsan, Ali; Briawan, Dodik; Riyadi, Hadi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The objective of this study was to assess compliance to small-quantity lipid-based nutrient supplements (SQ-LNS) and associated factors. The community-based non randomized controlled intervention was conducted among 117 infants aged six months old in Bangkalan district and received a daily 20 g SQ-LNS (n=58) or three pieces biscuit (n=59) for six months. In SQ-LNS group, the compliance was 71.7%, 62.7%, 59.3% over one, three, and six-month intervention. The proportion of infant with compliance as recommended (7 sachets SQ-LNS per week) was 68.6%, 34.3%, 18.6%. In Biscuit group, the proportion was 96.6%, 92.8%, 91.1% and compliance as recommended (21 pieces per week) was 94.9%, 93.2%, 91.5%. Logistic regression analysis showed that low mother education (OR=3.67; 95%CI:1.14-11.74), food secure household (OR=3.87; 95%CI:1.26-11.88), high household dietary diversity (OR=3.78; 95%CI:1.20-11.89), and low social economy status (OR=3.81; 95%CI:1.16-12.56) were significantly associated with compliance of SQ-LNS as recommended. The mean of day and proportion of recommended daily serving consumed were 3.3 days and 98.8%, in SQ-LNS group; while in Biscuit group were 3.5 days and 87.2%. Mother reported that side effect of consuming SQ-LNS and biscuit were children felt bored (60.3%, 13.6%), vomiting (43.1%, 18.6%), suffering diarrhea (15.5%, 1.7%), respectively. The reason of irregular provision of SQ-LNS and biscuit were vomiting at the early consumption period response, boring, and did not like the smell/taste of SQ-LNS or biscuit. Mother perceived that the benefit of SQ-LNS and biscuit was increase body immunity, weight gain, appetite, and child become more active.